Efek Senam Kaki Terhadap Penurunan Kadar Gula Darah Pada Penderita Diabetes Melitus Tipe 2 - Riyan Mulfianda; Nursaadah Nursaadah; M. Agus Fitra (Pusat Riset dan Inovasi Nasional, 2021)
Diabetes mellitus is a metabolic disorder caused by a lack of the hormone insulin. The hormone insulin is produced by a group of beta cells in the gland of the pancreas and plays an important role in glucose metabolism in body cells. According to the World Health Organization (WHO, 2013) 80% of DM sufferers in the world come from developing countries, one of which is Indonesia. The prevalence of DM in Indonesia reaches 4.7% of the national population and is expected to reach 5.9% by 2030. In general, the prevalence of DM in Aceh province is 1.8%. The purpose of this study was to determine the effect of Diabetes Mellitus Gymnastic Therapy on Decreased Blood Sugar Levels in the Elderly in Ceurih Village, Banda Aceh City. This study uses Quasi Experiment Design research design using one group pre test-post test design. The sampling technique uses total sampling by measuring blood sugar levels before and after diabetes exercises with a total sample of 16 people. Bivariate analysis uses paired t-test. The results showed that there was an Effect of Diabetes Mellitus Gymnastic Therapy on Decreased Blood Sugar Levels in the Elderly in Ceurih Village, Banda Aceh City with a statistical result of 0,000.